Pengaruh Penerapan Lean Manufacturing Terhadap Kinerja Produksi di PT. XYZ - Avira Septiana; Sarah khulillah; Cornelia Febryanti; Herdian Wibowo; Dwi Irwati (Program Studi Teknik Industri Fakultas Teknik Universitas Islam Makassar, 2025)
This study aims to analyze the effect of Lean Manufacturing implementation on production performance . Lean Manufacturing is a systematic approach to identifying and eliminating waste in the production process to improve company efficiency and productivity. The research methods used include direct observation, interviews, and analysis of production data before and after Lean Manufacturing implementation. The results indicate that Lean Manufacturing implementation successfully enhanced production process efficiency, reduced cycle times, and decreased waste such as waiting time, unnecessary movement, and defective products. Additionally, there was an increase in production output and employee job satisfaction. These findings are consistent with previous studies stating that Lean Manufacturing can significantly impact operational performance by improving quality, reducing costs, and increasing production speed. Therefore, Lean Manufacturing implementation is recommended as a sustainable strategy to enhance competitiveness and production performance in the manufacturing industry